The linguistic soyings of Abi –AL- Khatab AL- Akhfah In the book (Jamharat AL- Lugha) -study and Dictionary- - محمود محمد عيسى, أحمد (Journal of College of Education, 2021)
The importance of this research lies in collecting the soyings of a good scientist who is famous in Novel. He lived in the era of linguistics in the countryside and he book many from them. None of his writing reached us may be because it was told orally in the mosques and studying circles.            This research is divided into tow divisions: The first is about the study while the second is a dictionary as well as an introduction and a conclusion, we also wrote the resorces and references